2013
DOI: 10.1126/scisignal.2004014
|View full text |Cite
|
Sign up to set email alerts
|

Drug Synergy Screen and Network Modeling in Dedifferentiated Liposarcoma Identifies CDK4 and IGF1R as Synergistic Drug Targets

Abstract: Dedifferentiated liposarcoma (DDLS) is a rare but aggressive cancer with high recurrence and low response rates to targeted therapies. Increasing treatment efficacy may require combinations of targeted agents that counteract the effects of multiple abnormalities. To identify a possible multicomponent therapy, we performed a combinatorial drug screen in a DDLS-derived cell line and identified cyclin-dependent kinase 4 (CDK4) and insulin-like growth factor 1 receptor (IGF1R) as synergistic drug targets. We measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 92 publications
1
78
0
Order By: Relevance
“…IRS proteins transduce mitogenic, antiapoptotic, and antidifferentiation signals to the cell, mainly through the PI3K-AKT module (28). Although antioncogenic synergistic effects have been observed using either CDK4 and IGF1R inhibitors or CDK4 and PI3K inhibitors, no crosstalk between both pathways has been described (29)(30)(31)(32). The CDK4/ CDK6 inhibitor (PD0332991, palbociclib) has been approved for the treatment of breast cancer (33).…”
Section: Cdk4 Regulates Insulin Signaling In Vivo Via Irs2mentioning
confidence: 99%
“…IRS proteins transduce mitogenic, antiapoptotic, and antidifferentiation signals to the cell, mainly through the PI3K-AKT module (28). Although antioncogenic synergistic effects have been observed using either CDK4 and IGF1R inhibitors or CDK4 and PI3K inhibitors, no crosstalk between both pathways has been described (29)(30)(31)(32). The CDK4/ CDK6 inhibitor (PD0332991, palbociclib) has been approved for the treatment of breast cancer (33).…”
Section: Cdk4 Regulates Insulin Signaling In Vivo Via Irs2mentioning
confidence: 99%
“…Barretina and colleagues showed cell-cycle arrest and growth inhibition in two liposarcoma cell lines treated with CDK4 shRNA or the CDK4/6 inhibitor PD0332991 (19). A more recent study also reported that the addition of an IGF1R inhibitor to PD0332991 led to greater inhibition of cell-cycle progression and cell metabolic activity (20). However, detailed biochemical analyses and the preclinical in vivo effects of CDK4/6 inhibitors on liposarcoma xenograft models have not yet been described, and predictive biomarkers for CDK4/6 inhibitor activity are still lacking.…”
Section: Introductionmentioning
confidence: 88%
“…These numbers emphasize the significant enrichment of synergistic drug combinations compared with traditional experimental high-throughput screens (P < 1eÀ04; Supplementary Fig. S8A and S8B), which detect synergy in 4% to 14% of the drug pairs tested (16,34,35). A detailed description of the comparison can be found in the Supplementary Material (Section S6).…”
Section: Experimental Validation Of Selected Drug Combinationsmentioning
confidence: 99%
“…In addition, we assessed the PCI for 68 synergistic, additive, or antagonistic drug pairs identified in a combination screen performed in a tumor-derived liposarcoma cell line (DDLS817) considering 14 targeted compounds from distinct drug classes (16). This screen resulted in 14.3% synergistic, 38.5% additive, and 22% antagonistic combinations.…”
Section: Pci As a Tool For Inferring Synergistic Drug Combinationsmentioning
confidence: 99%
See 1 more Smart Citation